Non-Neuropathic Form of Mucopolysaccharidosis Type II: Clinical Cases - Nato D. Vashakmadze; Natalia V. Zhurkova; Leyla S. Namazova-Baranova; Nina V. Fedorova; Marina A. Babaykina (Вопросы современной педиатрии)
Background. Mucopolysaccharidosis (MPS) type II is an X-linked hereditary disease from the lysosomal storage diseases group. The absence or malfunctioning of the iduronate-2-sulfatase enzyme leads to disruption in glycosaminoglycans (GAG) degradation. The GAG accumulation in lysosomes leads to dysfunction of various tissues and organs. There are neuropathic (severe) and non-neuropathic (relatively mild) forms of the disease. Early diagnostics of non-neuropathic form of MPS II is quite difficult due to slow disease progression and because early symptoms are hard to notice. Clinical Cases Description. This article describes three clinical cases of non-neuropathic form of MPS II. Patients had following symptoms: non-rough facial features changes (gargoylism), hepatomegaly, hernias, recurrent otitis, non-inflammatory joint contractures, and cardiac valves involvement. The children height conformed to the age or was little lower than reference values. The described form of MPS II is characterized with the absence of cognitive impairment. Conclusion. Enzyme replacement therapy efficacy has been shown via disease progression slowing down, significant improvement of clinical symptoms and quality of life.